Supporting Australian clinical learners in a collaborative clusters education model: a mixed methods study - Thea F. van de Mortel; Lyn Armit; Brenton Shanahan; Judith Needham; Candy Brown; Eileen Grafton; Michelle Havell; Amanda Henderson; Laurie Grealish (BMC, 2020)
Abstract Background Nursing student numbers have risen in response to projected registered nurse shortfalls, increasing numbers of new graduates requiring transitional support and pressure on clinical placements. A Collaborative Clusters Education Model, in which Entry to Practice facilitators coach ward-based registered nurses to support students' and new graduates' learning, may address placement capacity. The research aim was to evaluate the acceptability of the Collaborative Clusters Education Model to stakeholders by examining their perceptions of the facilitators and barriers to the model in its implementation. Methods A convergent mixed methods evaluation approach was adopted. The study took place in a large Australian health service in south-east Queensland. Participants included Bachelor of Nursing students, Entry to Practice facilitators, ward-based registered nurses, academics and new graduates. A mixed methods design was used. Elements included an online survey of nursing students, and interviews with new graduates, Entry to Practice facilitators, ward-based registered nurses, and academics. Descriptive statistics were calculated on quantitative data. Thematic analysis was conducted on qualitative data. Results Participants included 134 (of 990) nursing students (response rate 13.5%), five new graduates, seven Entry to Practice facilitators, four registered nurses, and three nurse academics. Students rated facilitators' effectiveness highly (4.43/5 ± 0.75), although this finding is tempered by a low response rate (13.5%). For learners, the model provided access to learning experiences, although preferences for sources of support differed between students and new graduates, and further clarification of responsibilities was required. For other stakeholders, three themes emerged: students' and new graduates' integration into the workplace can promote learning; tensions arise in new ways to approach performance assessment; and aligning expectations requires high levels of communication. Conclusions This evaluation found that acceptability was good but at risk from limited clarity around roles and responsibilities. Further research into this model is recommended.